Study of A Family with Clinical Features and Inheritance Pattern of Nance Horan Syndrome - Sonal Patil; Kalpna Jain; Jaishri Murli Manoher; Vimla Beniwal (Delhi Journal of Ophthalmology)
Congenital cataract has various modes of inheritance. In Nance Horan syndrome, X linked recessive pattern of inheritance of congenital cataract is seen. Protein truncation mutation in an NHS gene located on Xp21.2-p22.3. could be associated with this syndrome. We report a case of Nance Horan syndrome family with bilateral congenital cataract with microcornea, strabismus, nystagmus, mental retardation, dysmorphic facies and dental anomalies. Treatment consists of surgery for cataract extraction, although results are poor.